Suara Genta dalam Ritual Persembahyangan Melasti oleh Umat Hindu di Blitar, Jawa Timur - Wahyuningsih, Indah; Kiswanto (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2025)
This study aims to determine the use and function of the bell in the Melasti prayer of Hindus in Blitar Regency. The bell in the Melasti prayer has an important role. The role of the bell in the series of Melasti prayers includes making tirta, eteh-eteh, nglarung sesaji, and sembahyang tri sandya. This study uses a qualitative method with an ethnographic approach. Alan P. Merriam in the Anthropology of Music, said that the use and function are references to examine the issue of how to use the bell, and its function in the Melasti prayer. Through the opening of the anthropological glasses, Merriam produced the use of the bell in the Melasti Prayer as an accompaniment to the Pandita's mantram and the five main functions of the bell in the Melasti Prayer, namely the Emotional Expression Function, Communication Function, Social and Religious Institution Validation Function, Physical Reaction Function, Hindu Community Integration Function. So that the bell in the Melasti prayer is not only religious music, but is able to create more space so that the bell can convey solemnity, human unity to communicate with Sang Hyang Widhi and culture.